The Effectiveness of Fractional Chalkboard Media in Reducing Misconceptions and Improving Learning Outcomes Among Elementary School Students - Aiman Khairun Nazata Dini (Journal of Education and Teaching Learning, 2026)
This study aimed to determine the effectiveness of the fraction shading board manipulative media in reducing misconceptions and improving mathematics learning outcomes among fourth-grade students at SD Muhammadiyah 3 Denpasar. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The sample consisted of 45 students divided into an experimental group (23 students) and a control group (22 students). The instruments used were misconception tests and mathematics learning outcome tests. Data were analyzed using the N-Gain test and the Independent Samples t-test. The results showed that the posttest mean score of the experimental group was higher than that of the control group. The N-Gain score of the experimental group was 0.55, falling into the moderate category, while the control group obtained 0.23, falling into the low category. Additionally, misconceptions in the experimental group decreased significantly. The hypothesis test yielded a significance value of 0.000 (p < 0.05). Therefore, the fraction shading board manipulative media were effective in reducing misconceptions and improving students’ mathematics learning outcomes.